Efficient and secure electronic evidence exchange scheme for internet of things - Xiao, Yulong; Chen, Liang (Frontiers in Physics, 2025)
With the rapid development of information technology, Internet of Things (IoT) is profoundly impacting various fields of the socio-economic landscape, driving the transformation of traditional industries towards intelligence. However, the widespread application of IoT has also led to a surge in electronic evidence, whose importance in the judicial field is increasingly prominent, but its characteristics such as ease of replication and leakage have posed new challenges for privacy protection. This paper focuses on the security and privacy issues of electronic evidence in IoT and proposes an efficient and secure interaction scheme based on chebyshev chaotic map, hash functions and XOR operations. Through a secure two-factor authentication mechanism, this scheme achieves identity verification between the user and the storage center, as well as confidentiality during the data transmission process. This has significant implications for the healthy development of IoT, judicial fairness and personal privacy protection. Experimental and theoretical analysis shows that the proposed scheme not only effectively resists various known attacks, but also performs excellently in terms of communication and computation costs, making it well-suited for IoT.